“The Society of Jesus and Portugal: 1540-1773. From Establishment to Extinction. A Historiographical Approach” - Manso, Maria de Deus (2021)
Perhaps one of the major topics that scholars working on the history of the Society of Jesus in Portugal find fascinating is the theme dealing with an apologetic and ideological history of this religious order whereby at times they see it as the stronghold of progress when it comes to teaching and for their work in the missions overseas or, to the contrary, they accuse it of having a universalist ambition that eventually led to the socio-political decline of the nations that hosted them. Using as a springboard the establishment of the Society of Jesus in Portugal and the breadth and depth of publications written by and on this religious order, I will reflect on how scholars hailing from the 19th, 20th, and 21st centuries analyzed 233 years of Jesuit presence in Portugal, namely, from its establishment in 1540 to its suppression in 1773